The Function of Classical African Literary Works: A Systemic Functional Analysis of Wole Soyinka’s Death and the King’s Horseman - Djimet, Issa; Abdoulaye, Kouago; Aubin, Guideng Kertemar (European Scientific Journal, ESJ, 2024)
This paper is about the systemic functional analysis of Wole Soyinka’s Death and the King’s Horseman, on the basis of the postulate that African classical literary works connote some significant functions. The methodology used in this analysis is the mixed method approach, which is a combination of both quantitative and qualitative linguistic data. Two extracts are therefore selected from the play on a qualitative basis, taking into account the relevance of the exchange in terms of information and the characters involved in the exchange. These are split into numbered analyzable units referred to as clauses in which the various mood components are meticulously and quantitatively identified. The results reveal that the extracts are essentially concerned with propositions, that is, the exchange of information about the rite; while some services are realized through proposals. Modal variables are profusely used in the extracts under consideration, highlighting interlocutors’ various attitudes and judgments regarding the traditional ritual of the king’s horseman death. The analysis of the exchange has uncovered the peck order defined by the colonial administrators whose behaviors are profoundly marked by prejudices regarding the rite. Thus, Soyinka’s play functions as a tool of information and education about African worldview.